Green social networking: concept and potential applications to initiate industrial synergies. (1st March 2016) - Ghali, Mohamed Raouf; Frayret, Jean-Marc; Robert, Jean-Marc
Abstract: This paper presents a conceptual analysis of computer-supported social networking and its potential applications for industrial ecology. More specifically, it introduces the concept of Green social networking (GSN), and analyzes the potential role of online social networking for stimulating social connections and enabling material flow compatibilities in a way that can lead to the formation of industrial synergies. Thus, this paper proposes a review of the role of social media and social networks in order to analyze their ability to stimulate the initiation of industrial synergies. This analysis provides a framework for creating a Web-based industrial synergy support system based on social network-style functionality. For industrial companies and their key stakeholders, this might serve as a system that helps forge partnerships and connections with like-minded others, and ultimately helps discover material flow compatibilities. It could also help post and distribute related information for an entire industry, which could improve the dissemination of knowledge related to industrial ecology. Finally, GSN could provide researchers interested in exploring the potential of social networks with a new and rich research domain, while bridging both online and offline connections between personal and business sectors.